El istmo invisible. Los casos de El Salvador y Nicaragua - Szente-Varga, Mónika (Acta Scientiarum Socialium, 2011)
The Invisible Isthmus. The Cases of El Salvador and Nicaragua During the eighties, the Socialist World paid intensive attention to Central America, particularly to the National Liberation Fronts in Nicaragua and El Salvador. However, this attention had an ideological background, which vanished with the change of political systems in Central-Eastern Europe. Since then, there has been a lack of interest towards the Isthmus. This essay therefore aims to „rescue” the region and to study recent history of Central America. It compares the political transitions of Nicaragua and El Salvador, as well as the implications these had on foreign policy, more preÂ¬cisely, on bilateral relations, bonds in Latin America, and nexus with other countries like Hungary.
Keywords: Nicaragua; El Salvador; National Liberation Front; political transition; Post-Cold War; foreign policy; nexus with European Union